Women, career, barrier and performance (A study on MNCs in Malaysia) - Nagarani, Seenivasa (Universiti Malaysia Sarawak (UNIMAS), 2011)
In Malaysian organizations mostly, the circumstances of promoting professional women to top management positions remains a sensitive subject over time. Even though the percentages of women entering the labor force are rising, the percentages of those who are holding higher managerial positions are still low. Hence, this research is important to find out the barriers to women career progression and determine how the barriers impact toward the employees’ job performance as well. The study is focusing at the Multinational Companies in Malaysia. Questionnaires were distributed and analyzed through frequency distribution, the Mean, Correlation, Regression as well as Factor Analysis; used to identify the interrelations and significant relationship between perceived barriers to women career progression and its impact toward job performance. The result shows that there is a significant relationship between dependent variables and job performance. There are five dependent variable factors were found to be a reason for barriers to women career progression. They are Glass Ceiling, Gender Stereotype, Sexual Discrimination, Lack of Mentorship and Gender Wage Gap.